Pengembangan Media Pembelajaran Melalui Website Berbasis Masalah Materi Sistem Reproduksi Kelas IX MTS Negeri Mamuju - Abdul Hamid (Universitas Negeri Makassar, 2023)
This study aim to Development Of Learning Media Through Website Problem Based Learning that is valid, practical, and effective. This study is a research and development with ADDIE development models, which consists of analyze, design, development, emplementation, and evaluation. The participant of this study was The Ninth (9th) Grade MTs Negeri 1 Mamuju with a total of 30 participants. The instruments used in this study were validation sheets to collect data validity of Development Of Learning Media Through Website Problem Based about content and product, observation sheets to collect data about practically, teacher and student response quetionnaires, and test on student result study. The Development Of Learning Media Through Website Problem Based Learning Materials Of Reproductive System were developed yhen tested for validity until it was declared valid by validator and then it was implemented in the classroom to determine the practically through the implantation observation, teachers an students response quetionnaires also the effectiveness of this product thorugh students learning outcomes results. The results of the observation of implementation met the validity status. Teacher response toward the product were positif, Students response toward the product were positif. The resulst of student learning outcome met the criteria effectiveness criteria because there found the increase value of student learning outcome. This, it can be concluded that the The Development Of Learning Media Through Website Problem Based Learning Materials Of Reproductive System At The Ninth (9th) Grade MTs Negeri 1 Mamuju have met valid, practical, and effective criteria.